SISTEM INFORMASI PENGOLAHAN DATA PREKLINIK PADA UNIT LITBANG RUMAH SAKIT HB. SA’ANIN PADANG - Ramadhani Ramadhani (JURNAL AKUNTANSI BARELANG, 2019)
HB. Sa’anin hospital Padang is the oldest Soul Hospital in western Sumatra, Every year HB.Sa’anin hospital always accepts medical students, nursing, psychiatric and others - to do pre-clinical The part or unit that performs data processing on student preclinics is LITBANG unit. In doing this preclinical data processing LITBANG units still use manual methods either through written notes or through word processing applications such as MS.Word and Ms.Excel. for preclinical data processing can be more quickly and efficiently, required an applicationusing PHP programming language to perform preclinical data processing on LITBANG HB unit. Sa'anin Hospital Padang.